Developing Inquiry-Based Practice Equipment of Heat Conductivity to Foster The Students’ Critical Thinking Ability - Agustini, Ratna; Suyatna, Agus (Jurnal Ilmiah Pendidikan Fisika Al-Biruni, 2018)
The purpose of this research is to develop inquiry-based practice equipment of heat conductivity to foster the students’ critical thinking ability. The research method employed was research and development (R & D). The development model used was ADDIE (Analysis-Design-Development-Implementation-Evaluation) model. Validation of product development was done by science education experts. Field-testing was conducted to the seventh-grade students of State Junior High school 3 (SMP Negeri 3) Blambangan Umpu Way Kanan. The data collection was done through observation, questionnaires, and tests of the effectiveness of fostering students' critical thinking ability. Data analysis was done through paired sample T-Test and independent sample T-Test. The results showed that the inquiry-based practice equipment of heat conductivity was effective in fostering the students’ critical thinking ability the value of N-gain 0.70 (high category). The equipment and its guides were considered interesting, practical, and useful by the students. So, it is concluded that the inquiry-based practice equipment of heat conductivity is able to foster the students' critical thinking ability.